2023
DOI: 10.3390/fi15040146
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Survey of Multi-Factor Authentication for Cloud Infrastructure

Abstract: The unauthorized usage of various services and resources in cloud computing is something that must be protected against. Authentication and access control are the most significant concerns in cloud computing. Several researchers in this field suggest numerous approaches to enhance cloud authentication towards robustness. User names and associated passwords have been a common practice for long as Single Factor Authentication. However, advancements in the speed of computing and the usage of simple methods, start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Security analysis can be used to assess the security of MFA implementations in cloud computing environments [93]. This analysis can help to identify and mitigate any potential security risks.…”
Section: Develop Mfamentioning
confidence: 99%
“…Security analysis can be used to assess the security of MFA implementations in cloud computing environments [93]. This analysis can help to identify and mitigate any potential security risks.…”
Section: Develop Mfamentioning
confidence: 99%
“…They reported that most papers were published in 2019 and, by country, the US, India, and China produced the largest number of MFA-related papers. Additionally, in 2023, Otta et al [10] conducted a survey on various factors that can be used for authentication to avoid threatening cloud infrastructure and proposed a method for configuring safe and efficient MFA.…”
Section: Introductionmentioning
confidence: 99%